The Quaternary History of Cumberland Sound, Southeastern Baffin Island: The Marine Evidence - Jennings, Anne (Géographie physique et Quaternaire, 1993)
ABSTRACTAcoustic and core data from Cumberland Sound show that glacial ice derived from the Foxe Sector (Amadjuak Dome) of the Laurentide Ice Sheet advanced to the continental shelf at the mouth of the sound during a late phase of the Foxe Glaciation. The basal lithofacies/acoustic unit (Ai/BUD) in the sound is a massive, black diamicton. On the basis of strati-graphic, acoustic, lithologie and faunal evidence, this unit is interpreted as till. The till is overlain by an ice proximal to ice distal glacial-marine sediment sequence termed the Davis Strait Silt (DSS). The influence of ice retreat is reflected in the foraminiferal assemblages of the DSS. Rapid sedimentation rates in the sound prevailed during deposition of the DSS as shown by the conformable geometry of the DSS. Accelerator Mass Spectrometry dates on molluscs and foraminifera and a single conventional 14C date on disseminated organic material from ice proximal sediment of the DSS (lithofacies B and lower lithofacies C) indicate that the ice retreated rapidly from its probable maximum position on the shelf no earlier than ca. 13,400 BP and into the fiords along the coast of the sound by ca. 8900 BP. Deposition of ice-distal glacial marine sediments (lower lithofacies D) continued in the sound until ca. 7600 BP as the ice margin rapidly retreated into the fiords. Between ca. 8900 BP and ca. 8000 BP, the foraminiferal fauna show that the influence of glacial ice is remote and that "Atlantic Water" impinges on the seafloor. Postglacial sedimentation began in the sound at ca. 7600 BP. Retreat of the ice margin onto land made the fiord basins available as sediment catchments. The reduced sedimentation rates in the sound during this interval are indicated by the change to onlapping basin fill geometry of the Tiniktartuq Silt and Clay (TS&C). Calcareous foraminifera disappear from the sediments by ca. 6300 BP and are replaced by agglutinated foraminifera reflecting "Arctic Water" conditions at the seafloor. The TS&C is presently being deposited in the sound.